Neoadjuvant chemoradiation for down staging of locally-advanced rectal cancer, and assessment of clinical response with digital rectal examination, magnetic resonance imaging and colonoscopy - Pawar, Sanjay R.; Koppad, Ravi; Ishwarappagol, Sheetal; Kallappa, Shashidhar; Guttedar, Dastayya (International Surgery Journal, 2024)
Background: In this era of total neoadjuvant treatment (TNT) followed by rectal preservation non-operative management (NOM) or wait and watch (WW) approach for non-metastatic locally-advanced rectal cancer (LARC), reliable and reproducible response evaluation to neoadjuvant therapies forms the cornerstone. Through this study, we try to evaluate clinical response of locally-advanced rectal cancer to neoadjuvant chemoradiation (CRT) in terms of downstaging and total mesorectal excision (TME), and the accuracy of digital rectal examination (DRE), magnetic resonance imaging (MRI) and colonoscopy in the assessment of clinical response to neoadjuvant CRT. Methods: Histologically proven locally advanced rectal adenocarcinoma patients, after pretreatment evaluation, were considered for neoadjuvant chemoradiation, i.e., intensity-modulated radiation therapy (IMRT) with 5-fluorouracil (5-FU) and leucovorin-based concurrent chemotherapy. Patients were evaluated 6-8 weeks after completion of CRT and clinical response assessed by means of DRE, colonoscopy and MRI of pelvis. Following surgery, pathological response was assessed on the final histopathological examination (HPE). Results: Twenty-two patients were accrued for this protocol, of which, 15 (68.2%) were male and 7 (31.8%) were female. Downstaging and TME was achieved in 90.9% of the patients. The sensitivity of DRE, colonoscopy and MRI to detect a complete response was 66.67% and specificity was 94.74%. There were no severe toxicities or deaths reported. Conclusions: Neoadjuvant concurrent chemoradiotherapy with bolus 5-FU and leucovorin is an accepted modality of treatment for locoregionally-advanced rectal cancer, which offers higher rates of downstaging and TME. Digital rectal examination, colonoscopy and MRI together can be reliably used to assess response following neoadjuvant CRT.